Chronology, evolution and morphology of plateau basalt eruptive centers in Avacha River Area, Kamchatka, Russia - Dirksen O.V.; Melekestsev I.V. (My University, 1999)
Nineteen Holocene eruptive centers (cinder cones with lava flows and maars) were located and described in the Avacha horst and anticline zone west of the East Kamchatka volcanic area. A tephrochronological study and the carbon-14 dating of soil and plant remains ranked the eruptive centers into three age groups: 11 000-7700, 3000-2500, and 1200-600 carbon-14 years B. P. The eruptive centers of these groups are believed to have been operating roughly synchronously with the periods of active magma injection in the East Kamchatka volcanic area. Eruptive histories were reconstructed for some of the volcanic centers. The structural and tectonic settings, geographical positions, and elevations of the centers were analyzed. The volume (1.1 km3) and weight (1.8 X 10^9 metric tons) of the erupted rocks were evaluated. The productivity of the plateau basalt volcanism was found to be 10-100 times lower than the plateau basalt productivity in the area of grabens and synclines, possibly, because of the more shallow basement in the horsts and because of the fact that the compression of the crust under uplifting conditions hampered the magma rise toward the surface. Most of the lavas and pyroclastics are basalts of the medium-potassic series, some having medium (54-62) and some elevated (65-70) Kmg values.
Keywords: 38.37.25 Вулканология; Бакенинг